IMPLEMENTASI METODE MAISURA DALAM MENINGKATKAN BACAAN AL-QUR’AN DI IIQ JAKARTA - Litakuna Karima (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
This research was motivated by students' lack of knowledge in understanding and mastering reading the Al-Qur'an. One way to answer this problem is that students must take part in maisura method tahsin learning or training which has applied the maisura method in learning the Al-Qur'an. The aim of this research is to analyze the implementation of Al-Qur'an learning and the factors that support and inhibit the maisura method at IIQ Jakarta. The method used in this study is a descriptive qualitative method by obtaining data naturally. Data collection techniques use observation, interviews, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation and conclusion verification. Interviews were conducted with the inventor of the maisura method, lecturers teaching tahsin of the maisura method and students. This study can be concluded that the implementation of learning the Qur'an by maisura method has met the good category. Female students are able to read the Qur'an with tartil and can produce outstanding students in the field of the Qur'an.